PENGARUH CITRA MEREK, HARGA DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK IMITASI - Anastasia Devi; Hari Susanta Nugraha; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2015)
This research is motivated by the circulation of imitation products that recently arise in some countries including Indonesia. This kind of business also keeps on growing thanks to the ever increasing demands of imitation product and resulted in increasing number of imitation goods purchase in society, especially among college students. Such decision is influenced by several factors, therefore this research will focus on the effect of brand image, price, and life style to the purchasing decision of Louis Vuitton’s imitation handbag. From the analysis it was found all three variables were positive and partially significant effect towards the purchasing decision of the imitation handbag purchase. The variable price coefficient was found to be the biggest, therefore making it the strongest factor for the Purchase Decision of Louis Vuitton’s imitation bag.